SISTEM INFORMASI E-RAPOR PADA MADRASAH ALIYAH SWASTAS (MAS) AL MA`ARIF NU MENGGUNAKAN METODE RAD (RAPID APPLICATION DEVELOPMENT) BERBASIS WEB - Prastya, Jacky Andre; Mayasari, Nova (Smart Education, 2025)
Abstract: The web-based e-Rapor information system is an innovative solution to improve the efficiency and accuracy of student grade management at the Al Ma'arif NU Private Islamic Senior High School (MAS). The assessment process that was previously carried out manually often faced obstacles such as recording errors, delays in delivering results, and difficulties in storing and archiving data. Therefore, this study aims to design and develop a web-based e-Rapor system by implementing the Rapid Application Development (RAD) method to accelerate the process of developing an effective and responsive system to user needs. The RAD method was chosen because it is able to accelerate the software development cycle with an iterative approach that involves users in every stage, from planning, designing, to implementation. This system is designed with main features including student data management, inputting grades by teachers, automatic grade processing, and presenting grade reports in digital form that can be accessed by guardians and schools. The technology used in developing this system includes a web-based framework that supports system flexibility and scalability. The results of the study indicate that the developed e-Rapor system is able to increase efficiency in processing grades, reduce the potential for recording errors, and accelerate the distribution of academic reports to students and parents. With this system, the school can manage student academic data in a more structured and transparent manner. The conclusion of this study confirms that the application of the RAD method in the development of a web-based e-Rapor system at MAS Al Ma'arif NU has a positive impact on improving the quality of academic data management and providing easy access to information for all related parties. Keywords: Information System, E-Report, Rapid Application Development, Web, Madrasah Aliyah Abstrak: Sistem informasi e-Rapor berbasis web dirancang untuk meningkatkan efisiensi, akurasi, dan transparansi dalam pengelolaan nilai siswa di Madrasah Aliyah Swasta (MAS) Al Ma’arif NU. Proses penilaian yang sebelumnya dilakukan secara manual sering menghadapi kendala seperti kesalahan pencatatan, keterlambatan penyampaian hasil, serta kesulitan dalam penyimpanan data akademik. Penelitian ini bertujuan untuk merancang dan mengembangkan sistem e-Rapor berbasis web menggunakan metode Rapid Application Development (RAD) guna mempercepat proses pengembangan sistem serta menyesuaikan fungsionalitasnya dengan kebutuhan pengguna. Metode RAD diterapkan karena memiliki pendekatan iteratif yang memungkinkan pengembangan perangkat lunak lebih cepat dengan keterlibatan aktif pengguna dalam setiap tahapannya, mulai dari perencanaan, perancangan, pembangunan, hingga implementasi. Sistem ini menyediakan fitur utama seperti manajemen data siswa, penginputan nilai oleh guru, pengolahan nilai otomatis, serta penyajian laporan akademik digital yang dapat diakses oleh siswa, wali murid, dan pihak sekolah. Teknologi berbasis web digunakan untuk memastikan fleksibilitas, kemudahan akses, serta keamanan data akademik yang tersimpan dalam sistem. Hasil penelitian menunjukkan bahwa sistem e-Rapor yang dikembangkan mampu meningkatkan efisiensi dalam pengelolaan nilai, mengurangi kesalahan pencatatan, serta mempercepat distribusi laporan akademik. Dengan penerapan sistem ini, pihak sekolah dapat mengelola data akademik secara lebih terstruktur, akurat, dan transparan, sehingga mendukung efektivitas proses pembelajaran dan evaluasi akademik. Kata kunci: Sistem Informasi, E-Rapor, Rapid Application Development, Web, Madrasah Aliyah